Suppression of extension of the photo-sensitive area for a planar-type front-illuminated InGaAs detector by the LBIC technique - 李永富 唐恒敬 李淘 朱耀明 姜佩璐 乔辉 李雪 龚海梅 (Journal of semiconductors, 2010)
To suppress the extension of the photo-sensitive area of a planar-type InGaAs detector, the structure of the detector was modified, and the small-diffusion-area diffusion method, circle-type covering contact and guard-ring were introduced. The laser-beam-induced-current （LBIC） technique was used to study the photo responsive characteristics of the photo-sensitive area of different detector structures. It was indicated that, by modifying the size of the diffusion area, the width of the circle-type covering contact, the distance between the guard-ring and the photo-sensitive area and the working status of the guard-ring, extension of the photo-sensitive area could be effectively suppressed, and the detector photo-sensitive area could be exactly defined.